KAJIAN INVESTASI KOTA SEMARANG - Fauzia Berliani Safitri; Wiwandari Handayani; Artiningsih Artiningsih (Jurnal Riptek, 2021)
Semarang City is designated as the fifth largest metropolitan city in Indonesia as well as the capital of Central Java Province. The average investment in Semarang City from 2014 to 2019 increased by 55% annually. Investors are interested in investing because Semarang City has a strategic and conducive location, is easily accessible, has a complete supporting infrastructure, there are several improvements aimed at improving the economy and having administrative guarantees. But by 2020 Semarang City experienced negative economic growth until it reached -1.61 due to the emergence of the COVID-19 pandemic. This caused Semarang to not reach its investment target by 2020. The fall in the pace of economic growth in 2020 caused the Semarang City Government to focus on stabilizing even improving the city's economy in 2021 and beyond. One of them is to increase investment activities in Semarang City. Based on content analysis in some of the supporting literature of this study, it can be known that the Semarang City Government in general needs to optimize adequate licensing, governance, human resources, databases and basic infrastructure. The government also needs to implement a climate of collaborative learning by involving the community, carrying out city rebranding activities and strengthening investment promotion through further study.